Pengaruh Penerapan Green Accounting, dan Audit Internal terhadap Kinerja Perusahaan (Studi pada Perusahaan Pertambangan yang terdaftar di Bei 2020-2023) - Pandiangan, Austin Alleyn; Siregar Sudjiman, Lorina; M.Hutabarat, Francis (Journal of Management and Bussines (JOMB), 2024)
This study aims to examine the impact of Green Accounting implementation and the role of internal audits on corporate performance, specifically focusing on mining companies listed during the 2020-2023 period. Using a purposive sampling method, the study analyzes 140 observations derived from 35 companies. This approach effectively explores information related to the disclosure of the GRI Index in sustainability reports and the background of internal audits as stated in companies' annual reports. Corporate performance is measured using Return on Assets (ROA) as the primary indicator. The analysis method applied is quantitative. The findings reveal that Green Accounting has a significant positive impact on ROA. Meanwhile, the impact of internal audits on ROA is positive but not statistically significant. Overall, the analysis of the effects of Green Accounting and internal audits on ROA indicates a significantly positive relationship. This study seeks to explore how Green Accounting practices and the role of internal audits with an accounting background influence corporate financial performance through the examination of financial reports. Keywords: Corporate Performance, Green Accounting, Internal Audit